Death Receptor 5 (TNFRSF10B) Is Upregulated and TRAIL Resistance Is Reversed in Hypoxia and Normoxia in Colorectal Cancer Cell Lines after Treatment with Skyrin, the Active Metabolite of Hypericum spp - Babinčák, Marián; Jendželovský, Rastislav; Košuth, Ján; Majerník, Martin; Vargová, Jana; Mikulášek, Kamil; Zdráhal, Zbyněk; Fedoročko, Peter (Cancers, 2021)
Skyrin (SKR) is a plant bisanthraquinone secondary metabolite from the Hypericum genus with potential use in anticancer therapy. However, its effect and mechanism of action are still unknown. The negative effect of SKR on HCT 116 and HT-29 cancer cell lines in hypoxic and normoxic conditions was observed. HCT 116 cells were more responsive to SKR treatment as demonstrated by decreased metabolic activity, cellularity and accumulation of cells in the G1 phase. Moreover, an increasing number of apoptotic cells was observed after treatment with SKR. Based on the LC-MS comparative proteomic data from hypoxia and normoxia (data are available via ProteomeXchange with the identifier PXD019995), SKR significantly upregulated Death receptor 5 (DR5), which was confirmed by real-time qualitative PCR (RT-qPCR). Furthermore, multiple changes in the Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-activated cascade were observed. Moreover, the reversion of TRAIL resistance was observed in HCT 116, HT-29 and SW620 cell lines, even in hypoxia, which was linked to the upregulation of DR5. In conclusion, our results propose the use of SKR as a prospective anticancer drug, particularly as an adjuvant to TRAIL-targeting treatment to reverse TRAIL resistance in hypoxia.
Keywords: TRAIL; hypoxia; skyrin; colorectal cancer; TRAIL resistance; proteomics; Hypericum; Death receptor 5